The police on Twitter: image management, community building, and implications for policing in Canada - O'Connor, Christopher D. (Policing and society, 2017)
Technology has always played an important role in policing. In recent years, various types of new social networking sites have become important tools for police departments. For example, social networking sites have been used to help solve crimes and communicate directly with the public circumventing the traditional news media. At the same time, the public can more easily communicate directly with, or about, the police. This article examines the use of Twitter by police departments on an everyday basis. Drawing on a content analysis of Canadian police departments’ Twitter accounts, this article discusses the types of information sent out to the public (i.e. on crimes/investigations, police work, safety/traffic, and community) as well as police attempts to interact with citizens (i.e. through invitations to attend events, asking for responses, and responding to and/or mentioning others). The findings suggest that Twitter was used to help manage the image of the police and build community. The implications of these findings are also discussed.